Introductory Medical-Surgical Nursing - Timby, Barbara Kuhn; Smith, Nancy E. (Nancy Ellen), 1949- (Wolters Kluwer Health, 2018)
"Publisher's Note: Products purchased from 3rd Party sellers are not guaranteed by the Publisher for quality, authenticity, or access to any online entitlements included with the product. This updated 12th Edition of Introductory Medical-SurgicalNursing and its online resources equips LPN/LVN students with the practical knowledge and skills necessary to provide safe and effective nursing care to adult medical-surgical clients in today's changing healthcare environment. This edition reflects current medical and nursing practice through accessible content enhanced by photos and illustrations that bring the information to life and reinforce learning."--
"In today's changing healthcare environment, nurses continue to face many challenges and opportunities"--
Nursing roles and responsibilities -- Client care concerns -- Foundations of medical-surgical nursing -- Caring for clients with multisystem disorders -- Caring for clients with respiratory disorders -- Caring for clients with cardiovascular disorders -- Caring for clients with hematopoietic and lymphatic disorders -- Caring for clients with immune disorders -- Caring for clients with neurologic disorders -- Caring for clients with sensory disorders -- Caring for clients with gastrointestinal disorders -- Caring for clients with endocrine disorders -- Caring for clients with breast and reproductive disorders -- Caring for clients with urinary and renal disorders -- Caring for clients with musculoskeletal disorders -- Caring for clients with integumentary disorders -- Caring for clients with psychobiologic disorders.
Includes bibliographical references and index.
Keywords: Nursing; Surgical nursing